Decoding polyphase migmatites using geochronology and phase equilibria modelling - Yakymchuk, C.; Brown, M.; Clark, C.; Korhonen, F.; Piccoli, P.; Siddoway, C.; Taylor, Richard; Vervoort, J. (Blackwell Publishing Inc., 2015)
In this study, in situ U–Pb monazite ages and Lu–Hf garnet geochronology are used to distinguish mineral parageneses developed during Devonian–Carboniferous and Cretaceous events in migmatitic paragneiss and orthogneiss from the Fosdick migmatite–granite complex in West Antarctica. SHRIMP U–Pb monazite ages define two dominant populations at 365–300 Ma (from cores of polychronic grains, dominantly from deeper structural levels in the central and western sectors of the complex) and 120–96 Ma (from rims of polychronic grains, dominantly from the central and western sectors of the complex, and from monochronic grains, mostly from shallower structural levels in the eastern sector of the complex). For five paragneisses and two orthogneisses, Lu–Hf garnet ages range from 116 to 111 Ma, c. 12–17 Ma older than published Sm–Nd garnet ages of 102–99 Ma from three of the same samples. Garnet grains in the analysed samples generally have Lu-enriched rims relative to Lu-depleted cores. By contrast, for three of the same samples, individual garnet grains have flat Sm concentrations consistent with high-T diffusive resetting. Lutetium enrichment of garnet rims is interpreted to record the breakdown of a Lu-rich accessory mineral during the final stage of garnet growth immediately prior to the metamorphic peak, and/or the preferential retention of Lu in garnet during breakdown to cordierite in the presence of melt concomitant with the initial stages of exhumation.Therefore, garnet is interpreted to be part of the Cretaceous mineral paragenesis and the Lu–Hf garnet ages are interpreted to record the timing of close-to-peak metamorphism for this event. For the Devonian–Carboniferous event, phase equilibria modelling of the metasedimentary protoliths to the paragneiss and a diatexite migmatite restrict the peak P–T conditions to 720–800 °C at 0.45–1.0 GPa. For the Cretaceous event, using both forward and inverse phase equilibria modelling of residual paragneiss and orthogneiss compositions, the P–T conditions after decompression are estimated to have been 850–880 °C at 0.65–0.80 GPa. These P–T conditions occurred between c. 106 and c. 96 Ma, determined from Y-enriched rims on monazite that record the timing of garnet and biotite breakdown to cordierite in the presence of melt. The effects of this younger metamorphic event are dominant throughout the Fosdick complex.